IMPLEMENTASI HUKUM LINGKUNGAN DALAM PERENCANAAN TATA RUANG KOTA PAMEKASAN - Umi Supraptiningsih (Karsa: Journal of Social and Islamic Culture)
AbstracThe city master plan connecting to its interior design has been the major requirement to develop a city. It comprises both private and public interest development. Therefore, every city development must intentionally consider environment harmony and balance. To carry out this, the government applies a tight development license. Ijin Lingkungan (environment care license) as a means of environment conservation, has not been ruled as a comprehensive environment care license. This license refers to a dual license systems---industrial license and Hinder Ordonannantie. On the other hand, Stb. 1926 No. 226 is not used any longer  as a reference of improving the system of environment care license. The government also recommends a continuity development. It is proportionally  characterized by three pillars---economic, social and environment conservation developmentsKata-kata kunciImplementasi, Hukum Lingkungan, Perencanaan Tata Ruang Kota